Are the recommendations for post-operative antibiotics in patients with grade I or II acute calculous cholecystitis being applied in clinical practice?. Issue 7 (July 2020) - Dembinski, Jeanne; Guérin, Orlane; Slim, Karem; Navarro, Francis; Paquet, Jean-Christophe; Tuech, Jean-Jacques; Pocard, Marc; Mauvais, François; Faucheron, Jean-Luc; Regimbeau, Jean-Marc
Abstract: Background: There is a level-1 evidence indicating that postoperative antibiotics are unnecessary following cholecystectomy for grade I or II acute calculous cholecystitis (ACC). We wanted to evaluate the applications of this recommendation in clinical practice four years after the original publication in ABCAL-participating centers. Methods: A retrospective analysis of patients operated for grade I or II ACC from January to December 2016 in ABCAL-participating centers was performed. Inclusion criteria were the same as for the ABCAL-study. The primary endpoint was the postoperative antibiotic administration rate. The secondary endpoints were postoperative outcomes. Results: Of the 283 patients included, 64% received postoperative antibiotics. Only 19% received antibiotics after POD1. The perioperative outcomes were similar between those that did or did not receive antibiotics after POD1. The median [range] length of stay was significantly shorter in patients who did not receive postoperative antibiotics (4 days [1–20]) compared to the others (6 days [1–50], p > 0.001). Conclusion: Despite strong recommendations included in the Tokyo 2018 guidelines, the results of the ABCAL-study are poorly applied even if the absence of postoperative antibiotics has no impact on morbidity. It is important to stress that postoperative antibiotics are not necessary after cholecystectomy for grade I or II ACC.